Early, Noninvasive Clinical Indicators of Kidney Prognosis in Primary Nephrotic Syndrome: A Retrospective Exploratory Study - Keiji Fujimoto; Takatoshi Haraguchi; Sho Kumano; Keita Yamazaki; Nobuhiko Miyatake; Kanae Nomura; Kiyotaka Mukai; Kazuaki Okino; Norifumi Hayashi; Hiroki Adachi; Hitoshi Yokoyama; Yasuo Iida; et al. (International Journal of Nephrology)
This retrospective exploratory study aimed to identify early clinical indicators of kidney prognosis in primary nephrotic syndrome (NS). Univariate Cox proportional hazards regression analysis identified clinical parameters in the 2-month period after initiating immunosuppressive therapy (IST); it predicted 40% reduction in the estimated glomerular filtration rate (eGFR) in 36 patients with primary NS. Time-dependent receiver operating characteristic curve analysis was used to evaluate the performance of the predictors for the cumulative incidence of 40% reduction in the eGFR up to 8 years after initiating IST. The mean follow-up period was 71.9 months. The eGFR was reduced by 40% in four patients. Significant predictors for time to 40% reduction in the eGFR were as follows: an increase in the serum soluble urokinase plasminogen activator receptor (s-suPAR) 2 months after initiating IST (Δs-suPAR (2M); hazard ratio (HR) for every 500 pg/mL increase: 1.36, P=0.006), s-suPAR at 2 months after initiating IST (s-suPAR (2M); HR for every 500 pg/mL increase: 1.13, P=0.015), urinary protein-to-creatinine ratio (u-PCR) (u-PCR (2M); HR for every 1.0 g/gCr increase: 2.94, P=0.003), and urinary liver-type fatty acid-binding protein (u-L-FABP) (u-L-FABP (2M); HR for every 1.0 μg/gCr increase: 1.14, P=0.006). All four factors exhibited high predictive accuracy for cumulative incidence of 40% reduction in the eGFR up to 8 years after initiating IST, with areas under the receiver operating characteristic curve of 0.92 for Δs-suPAR (2M), 0.87 for s-suPAR (2M), 0.93 for u-PCR (2M), and 0.93 for u-L-FABP (2M). These findings suggest that Δs-suPAR (2M), s-suPAR (2M), u-PCR (2M), and u-L-FABP (2M) could be useful indicators of initial therapeutic response for predicting kidney prognosis in primary NS.